Baixa qualidade de vida como um critério adicional para o diagnóstico clínico de insuficiência cardíaca na atenção primária - Arueira, Helena Barreto (2010)
Heart failure (HF) is a condition pandemic whose prevalence increases with aging, having a major impact on quality of life (QOL). The clinical diagnosis of IC has low accuracy and in primary care, the access to diagnostic methods is limited. OBJECTIVE: To estimate the association of the complaint of breathlessness, fatigue and edema of bilateral lower limbs (emi) - symptomatic triad of HF, with dimensions of QOL in a population assisted by the Family Medical Program (FMP) from Niteroi. METHODS: Cross-sectional study from the study CAMELIA involving families assisted by the FMP of Niteroi. Were included 455 participants from the study Camellia with thirty years or more, assessed by questionnaire, medical consultation and blood tests and urine. RESULTS: The fatigue was more prevalent (56.9%), followed by breathlessness (22.6%) and by emi (16.9%). There was an independent association of asthma/bronchitis, anemia, depression, obesity, diabetes mellitus, hypertension, myocardial infarction, atrial fibrillation, stroke, angina and smoking and statistically significant "breathlessness" and "fatigue" with all domains of the SF-36 (Medical Outcomes Study 36-item Short Form Health Survey), except for "emotional aspects and "breathlessness" (p <0.10). CONCLUSION: The association of the presence of breathlessness and fatigue to the low QOL can increase the positive predictive value for diagnosis of IC, being a possible alternative to prioritize patients access to more accurate diagnostic methods in primary care setting.